2020
DOI: 10.1111/ijfs.14657
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the role of selenium‐enriched rice protein hydrolysates in the regulation of Pb2+‐induced cytotoxicity: an in vitro Caco‐2 cell model study

Abstract: Lead (Pb), a well-known toxic metal, has a potential of adverse effects on human health. Selenium (Se) can reduce the toxicity caused by heavy metals. In this study, we investigated the protection mechanism of the purified Se-enriched rice protein hydrolysates (SPHs-2) on the Pb 2+-induced cytotoxicity. A Caco-2 cell model was established to characterise the effect of SPHs-2 on Pb 2+ absorption in the simulated small intestine. Results showed that 1000 lg mL À1 of SPHs-2 treatment could significantly increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In addition to simple seleno‐amino acids, some biological potentials of Se‐containing peptides derived from cereals have also been characterized, including antioxidant, immunomodulatory, and hepatic protective activities (Zhang et al., 2021; Zhang et al., 2020) Compared to its sulfur analogue, the peptide with the sequence SeMet‐Pro‐Ser in brown rice protein hydrolysate had a much higher antioxidant activity (Liu et al., 2015, 2019). We found that SeMet and Se‐containing peptides from Se‐enriched rice protein hydrolysate protected PC12 and RAW264.7 cells from Pb 2+ ‐induced cytotoxicity via up‐regulation of the antioxidant system, inhibited apoptosis through the caspase‐dependent mitochondrial pathway (Fang et al., 2017; Xu et al., 2016), and retarded Pb 2+ intestinal absorption in the Caco‐2 model (Zhu et al., 2020). The Se‐enriched rice protein hydrolysate fraction (containing SeMet‐ Pro‐Ser, Met‐MeSeCys‐Glu, and SeMet‐MeSeCys‐Glu) was more effective in attenuating Pb 2+ ‐induced inflammatory response than SeMet and selenite in RAW264.7 macrophages, and it inhibited immunotoxicity via the NF‐κB/MAPK signaling pathways (Wu et al., 2021).…”
Section: Selenium Species In Cereals and Human Healthmentioning
confidence: 99%
“…In addition to simple seleno‐amino acids, some biological potentials of Se‐containing peptides derived from cereals have also been characterized, including antioxidant, immunomodulatory, and hepatic protective activities (Zhang et al., 2021; Zhang et al., 2020) Compared to its sulfur analogue, the peptide with the sequence SeMet‐Pro‐Ser in brown rice protein hydrolysate had a much higher antioxidant activity (Liu et al., 2015, 2019). We found that SeMet and Se‐containing peptides from Se‐enriched rice protein hydrolysate protected PC12 and RAW264.7 cells from Pb 2+ ‐induced cytotoxicity via up‐regulation of the antioxidant system, inhibited apoptosis through the caspase‐dependent mitochondrial pathway (Fang et al., 2017; Xu et al., 2016), and retarded Pb 2+ intestinal absorption in the Caco‐2 model (Zhu et al., 2020). The Se‐enriched rice protein hydrolysate fraction (containing SeMet‐ Pro‐Ser, Met‐MeSeCys‐Glu, and SeMet‐MeSeCys‐Glu) was more effective in attenuating Pb 2+ ‐induced inflammatory response than SeMet and selenite in RAW264.7 macrophages, and it inhibited immunotoxicity via the NF‐κB/MAPK signaling pathways (Wu et al., 2021).…”
Section: Selenium Species In Cereals and Human Healthmentioning
confidence: 99%
“…Additionally, Shang et al [78] demonstrated that selenium-enriched Bacillus subtilis protected carp from mercury-induced inflammation, effectively reducing mercury toxicity. Zhu et al [79] investigated that selenium-enriched rice protein hydrolysates reduced lead-induced cytotoxicity via slowing the accumulation of lead in cells.…”
Section: The Function Of Alleviating the Toxicity Of Heavy Metalsmentioning
confidence: 99%
“…Interestingly, Se-methionine played a key role in regulating the intestinal absorption of Pb 2+ . 73 Se-Enriched Spirulina platensis protein (SSPP) could inhibit high-glucose induced calcification damage of MOVAS cells by inhibiting MAPKs and the PI3K/Akt pathway, which indicated that SSPP had potential as an effective treatment for cerebrovascular and cardiovascular diseases. 7 SSPP also could inhibit oxygen-glucose deprivation-induced apoptosis and toxicity of hippocampal neurons by regulating the opening and closing of the mitochondrial permeability transition pore, which demonstrated that SSPP had potential application as an effective preventive treatment for ischemic brain injury.…”
Section: Bioactivities Of Se-enriched Proteins and Their Hydrolysatesmentioning
confidence: 99%